Training for Making Wordwall Learning Media for Teachers in SMK PGRI Kuwu, Grobogan Regency - Wibisono, Arif; Wijayanto, Wijayanto; Menarianti, Ika (Patria : Jurnal Pengabdian Kepada Masyarakat, 2023)
It doesn't feel like the Covid-19 pandemic that has lasted for 2 years has changed the learning model that we have known so far, namely face-to-face, although the blended learning model that combines conventional models with online learning has been introduced as an evolutionary model, but with the pandemic forcing it to happen. for teachers to immediately adapt and implement it in the schools where they teach as a need that must be met considering the demands of the community who want educators and educational institutions to be able to provide quality education in the midst of this crisis. As an affected educational institution, SMK PGRI Kuwu strives to continue to provide quality learning by applying the blended learning model (Purnomo et al., 2016). After communicating with the service team from PGRI Semarang University, consensus was obtained that the problems faced by partners could more or less be solved by implementing information technology in learning, one of which was the introduction of interactive learning media Wordwall with additional Gamification learning models (Putri, 2020). The application and learning model itself uses a Cloud system or Cloud Computing where between teachers and beneficiaries of learning or students can use information technology devices that vary depending on availability, and do not require device specifications with special and updated technology, the most important thing is the availability of internet network connectivity. Sari Yarza, 2021). Wordwall specifically can be used to create learning media such as quizzes, matchmaking, pairing, anagrams, word randomization, word search, word grouping, and several other additional features such as questions and answer results that can be printed on paper making it easier for teachers and students to document results. work as a task (Hasram, 2021). Through this introduction activity or PKM (Community Partnership Program), it is hoped that teachers and lecturers at SMK PGRI Kuwu can implement it in their learning classes, and are expected to be able to overcome the learning gap that has occurred as a result of the Covid-19 pandemic. The results of the ongoing activities in the form of mentoring and evaluation training, carried out for 3 days which were carried out in a blended manner (offline and online) with the results and responses of the activity participants showing positive indications as indicated by the reapitulation of the questionnaire results of participants' responses to this training activity which showed an average result of 3, 85 on a scale of 4 which indicates a good response or a positive response to the implementation of the training activities.